Embedding telephone therapy in statutory mental health services: a qualitative, theory-driven analysis. Issue 1 (December 2016) - Bee, Penny; Lovell, Karina; Airnes, Zerena; Pruszynska, Anna
Abstract Background Telephone-administered cognitive behavioural therapy (T-CBT) has attracted international recognition as a potential means of providing effective psychological treatment whilst simultaneously lowering costs, maximizing service efficiency and improving patient access to care. A lack of rigorous exploration of therapist perspectives means that little is known about professional readiness to adopt such delivery models, or the work that may be involved in ensuring successful implementation. Methods This paper reports on a qualitative exploration of professional views of high intensity T-CBT. Semi-structured interviews with 18 UK accredited Cognitive Behavioural Therapists with nursing or allied health backgrounds were collected and analysed according to Normalisation Process Theory, a contemporary and empirically-derived theory of health technology implementation. Results Despite increasing research effort seeking to determine the effectiveness of T-CBT, the clinical rationale for its use remains insecure. Professional perceptions of T-CBT as a high risk delivery strategy emerge as a key factor delaying T-CBT routinisation in practice. T-CBT champions draw on experiential knowledge to demonstrate that remote services can add value, a key factor being the recognition that telephone-mediated services can provide viable access for hard to reach populations. T-CBT uptake will be facilitated by i) the modification of existing protocols to address new methods of exchanging information and data, and (ii) greater clarification of the reach and span of telephone therapies, including the most appropriate division of labour across different service levels and settings. Conclusions The integration and normalisation of high intensity T-CBT into mental health services demands greater recognition and redress of the existing socio-technical matrices within which nursing and allied health practitioners work. The future spread of higher intensity T-CBT is contingent upon the willingness of service managers to support staff in the delivery and governance of non-face-to-face therapy models. Clear delineation of the role and scope of T-CBT and the extent to which it will extend or replace existing provision is required.